Association between patient survival following reoperation after total hip replacement and the reason for reoperation: an analysis of 9, 926 patients in the Swedish Hip Arthroplasty Register. (4th May 2019) - Cnudde, Peter; Bülow, Erik; Nemes, Szilard; Tyson, Yosef; Mohaddes, Maziar; Rolfson, Ola
Abstract : Background and purpose — The association between long-term patient survival and elective primary total hip replacement (THR) has been described extensively. The long-term survival following reoperation of THR is less well understood. We investigated the relative survival of patients undergoing reoperation following elective THR and explored an association between the indication for the reoperation and relative survival. Patients and methods — In this observational cohort study we selected the patients who received an elective primary THR and subsequent reoperations during 1999–2017 as recorded in the Swedish Hip Arthroplasty Register. The selected cohort was followed until the end of the study period, censoring or death. The indications for 1st- and eventual 2nd-time reoperations were analyzed and the relative survival ratio of the observed survival and the expected survival was determined. Results — There were 9, 926 1st-time reoperations and of these 2, 558 underwent further reoperations. At 5 years after the latest reoperation, relative survival following 1st-time reoperations was 0.94% (95% CI 0.93–0.96) and 0.90% (CI 0.87–0.92) following 2nd-time reoperations. At 5 years patients with a 1st-time reoperation for aseptic loosening had higher survival than expected; however, reoperations performed for periprosthetic fracture, dislocation, and infection had lower survival. Interpretation — The relative survival following 1st- and 2nd-time reoperations in elective THR patients differs by reason for reoperation. The impact of reoperation on life expectancy is more obvious for infection/dislocation and periprosthetic fracture.